The future of India's rural markets : a transformational opportunity - Sinha, Kunal (Emerald Publishing Limited, 2023)
A billion aspirational people, connected by technology, confident of their cultural and consumption power. If there is any group that has the potential to radically redefine a nation, it is rural Indians. By 2036, India is projected to be home to 1.52 billion people - having overtaken China around 2031 - with 931 million people still living in villages. Rural India is simply too large and too fast growing an agglomeration to ignore. This book maps their transformation, and shows how to realize their social and economic promise. It is a timely and important new work, ideal for students, scholars, marketing practitioners, and policy makers.